Combined Antiapoptotic and Antioxidant Approach to Acute Neuroprotection for Stroke in Hypertensive Rats. Issue 8 (August 2013) - Ord, Emily NJ; Shirley, Rachel; McClure, John D; McCabe, Christopher; Kremer, Eric J; Macrae, I Mhairi; Work, Lorraine M
We hypothesized that targeting key points in the ischemic cascade with combined neuroglobin (Ngb) overexpression and c-jun N-terminal kinase (JNK) inhibition (SP600125) would offer greater neuroprotection than single treatment after in vitro hypoxia/reoxygenation and in a randomized, blinded in vivo experimental stroke study using a clinically relevant rat strain. Male spontaneously hypertensive stroke-prone rats underwent transient middle cerebral artery occlusion (tMCAO) and were divided into the following groups: tMCAO; tMCAO + control GFP-expressing canine adenovirus-2, CAVGFP; tMCAO + Ngb-expressing CAV-2, CAVNgb; tMCAO + SP600125; tMCAO + CAVNgb + SP600125; or sham procedure. Rats were assessed till day 14 for neurologic outcome before infarct determination. In vitro, combined lentivirus-mediated Ngb overexpression + SP600125 significantly reduced oxidative stress and apoptosis compared with single treatment(s) after hypoxia/reoxygenation in B50 cells. In vivo, infarct volume was significantly reduced by CAVNgb, SP600125, and further by CAVNgb + SP600125. The number of Ngb-positive cells in the peri-infarct cortex and striatum was significantly increased 14 days after tMCAO in animals receiving CAVNgb. Neurologic outcome, measured using a 32-point neurologic score, significantly improved with CAVNgb + SP600125 compared with single treatments at 14 days after tMCAO. Combined Ngb overexpression with JNK inhibition reduced hypoxia/reoxygenation-induced oxidative stress and apoptosis in cultured neurons and reduced infarct and improved neurologic outcome more than single therapy after in vivo experimental stroke in hypertensive rats.